Double Taxation Avoidance Agreement (Tax Treaty) Against International Transactions According to the Islamic Economic Perspective - Firqotus Sa'idah; Tulus Suryanto (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Holding a Double Taxation Avoidance Agreement (P3B) or a Tax treaty is to avoid double taxation. The presence or absence of this tax treaty greatly affects investors’ profits in international trade transactions. International transactions are needed by every country because with international transactions a country will have the opportunity to increase its economic growth. Through this international trade, a country will have the ability to expand its consumption possibilities. In the agreement, the avoidance of double taxation must also meet the principles that apply in taxes and must also meet the principles of Islamic economics and the conditions of tax collection according to Islamic principles. The purpose of this research is the analysis of double taxation avoidance agreements in international transactions according to the perspective of Islamic economics. In this research, the researcher uses the type of library research. The data collection method is in the form of documentation. The documentation that the author does is looking for documents or data that the author considers important to be taken, in the form of newspaper/magazine articles, journals, libraries, brochures, the internet, and books. This study concluded that the taxation method as part of the method in increasing state revenue administratively must be viewed as a universal method that should not be diverted towards favoring a particular person or entity. Simply, double taxation has unfair treatment because there are still unilateral methods that do not provide justice for citizens who have dual citizenship. The principle of justice is an important pillar in Islamic economics.